ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU BERUTANG MASYARAKAT MUSLIM DI KECAMATAN SELEBAR - wahyunita sari, sherly; Desi Isnaini; Herlina Yustati (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the influence of economic needs, credit availability, and environmental factors on the debt behavior of Muslim customers of PNM Mekaar in Bengkulu City. This study uses a quantitative approach with an explanatory research type. Data were obtained from 80 respondents selected using a purposive sampling technique, with the criteria being active Muslim female customers who have taken out financing. Data collection was carried out by distributing questionnaires with a five-point Likert scale. Data analysis was carried out using IBM SPSS Statistics through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that economic needs have a positive and significant effect on debt behavior, indicating that pressures for household needs and business capital encourage people to use financing as a financial solution. Credit availability also has a positive and significant effect on debt behavior, indicating that easy access to PNM Mekaar financing increases people's tendency to borrow. Conversely, environmental factors have a negative and significant effect on debt behavior, indicating that a good social and family environment can reduce the tendency to borrow. Overall, this study confirms that economic factors act as the main driver of debt behavior, while environmental factors function as a controller, in line with Islamic economic principles which emphasize caution and responsibility in debt.